1992
DOI: 10.1093/jnci/84.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Vimentin and Keratins by Human Melanoma Tumor Cells: Correlation With Invasive and Metastatic Potential

Abstract: These findings show a correlation between the coexpression of vimentin with K8 and K18 keratins and the invasive and metastatic behavior of three representative human melanoma cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 0 publications
8
113
0
3
Order By: Relevance
“…We also observed down-regulation of vimentin, which is commonly up-regulated in cancers, including HCC, and was shown to decrease significantly in HCC cells upon miR-122 expression (14,16). Vimentin is a marker for mesenchymal cells and is positively associated with invasiveness and metastatic potential (37)(38)(39). Although not previously identified as a direct target, the vimentin 3ЈUTR does contain a 7-mer-m8 seed site, suggesting it may indeed be a direct miR-122 target.…”
Section: Resultsmentioning
confidence: 63%
“…We also observed down-regulation of vimentin, which is commonly up-regulated in cancers, including HCC, and was shown to decrease significantly in HCC cells upon miR-122 expression (14,16). Vimentin is a marker for mesenchymal cells and is positively associated with invasiveness and metastatic potential (37)(38)(39). Although not previously identified as a direct target, the vimentin 3ЈUTR does contain a 7-mer-m8 seed site, suggesting it may indeed be a direct miR-122 target.…”
Section: Resultsmentioning
confidence: 63%
“…Many epithelial cells express cytokeratin proteins K8, K18 and K19 (Oshima et al, 1988). Overexpression of cytokeratins with vimentin can lead to increased cell migration (Thompson et al, 1992;Chu et al, 1996), while overexpression of a dominant negative mutant K18 has been reported to reduce migratory ability in melanoma cells (Hendrix et al, 1992). These data raise the possibility that BAG-1 may promote cell migration through cooperation with these cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 98%
“…The human cutaneous (C81-61 and C8161) and uveal melanoma (OCM-1A, C918, MUM-2B, and MUM-2C) cell lines have been characterized previously according to their phenotype, invasive and metastatic potential, and clinical significance. C8161, C918, and MUM-2B cells are highly aggressive, whereas C81-61, OCM-1A, and MUM-2C are poorly aggressive melanoma cells (6,14,15). Human umbilical vein endothelial cells (HUVECs) were maintained in DMEM, 10% FBS, 1ϫ Mitoϩ (Collaborative Biomedical, Bedford, MA), and 0.1% gentamicin sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration in whole-cell lysates from the different cultures were determined by using a microbicinchoninic acid protein assay (BCA, Pierce) and equal amounts of protein for each cell line loaded onto 7.5% reducing sodium-dodecylsulfate polyacrylamide gels for electrophoresis. The separated proteins were transblotted onto Immobilon-P membranes (Millipore), which subsequently were probed with antibodies to human VE-cadherin (Transduction Laboratories, Lexington, KY), CD-31, or TIE-1 (R&D Systems), and detected as described (14).…”
Section: Methodsmentioning
confidence: 99%